Functional Analysis Contingencies on Precursors: Response Hierarchy Relationship Hypotheses - Apamo-Gannon, BCBA, Jescah (North American Journal of Medicine and Science, 2016)
Function-based interventions are effective in the treatment of severe problem behaviors. Functional analyses methodologies may present risks associated with behaviors under investigation. Researchers continue to explore alternatives for eliminating these risks. Identification of potential functions of less severe behaviors (i.e., precursors) that reliably precede more severe behavior may facilitate in the development of effective interventions (Smith & Churchill, 2002). In the current study, two experiments were conducted to treat challenging behaviors displayed by a 20-year-old woman with autism. Hypothesized maintaining consequences of precursor to the participant’s more severe behavior (self-injurious behavior; SIB and aggression) were identified in Experiment 1. Prior functional analysis contingencies of the participants SIB and aggression guided the development of a treatment package consisting of differential reinforcement, functional communication training- FCT, extinction, and response interruption and redirection (RIRD). The treatment package was utilized in experiment 2 to treat precursors hypothesized to belong in the same response class as the participant’s SIB and aggression. Results indicated a decrease in the frequency of SIB and aggression suggesting precursor analysis to be a promising alternative for reducing risks associated with FAs. [N A J Med Sci. 2016;9(4):141-150. DOI: 10.7156/najms.2016.0904141] Key Words: functional analysis, FCT, indirect assessments, precursor, self-injurious behavior, extinction